Impact of Covid-19 on Profitability in Kompas100 Index Companies - Anisah Abni; Agus Munandar; Audita Shasabilla Amin (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
The study was conducted to see the impact of the Covid-19 pandemic on the profitability of the industries incorporated in the Kompas100 index. There is also profitability using Return on Assets (ROA) and Return on Equity (ROE). The author sees 2 situations that change the situation the most, namely before and after the virus was announced. The author takes the entire population as well as all industries that are available and listed on the Indonesia Stock Exchange in 2019-2020. This research uses a quantitative descriptive approach and uses secondary information. The results obtained show that there is a large comparison of the ROA and ROE profitability ratios during the pandemic. Looking at the results of previous research and reviews, the results that the authors get are information related to the impact of the Covid-19 virus on the Kompas100 index on company profitability. A comparison needs to be considered because of changes in the period before and during the pandemic, to the return on assets (ROA) and return on equity (ROE) of the Kompas100 industry. Pay attention to profitability in the period before the Covid-19 pandemic.